SPONTANEOUS MISCARRIAGE AMONG 325 VIABLE PREGNANCIES COMPLICATED BY VAGINAL BLEEDING IN THE FIRST TWENTY WEEKS OF GESTATION - M. S. BASAMA, FAISAL; Crosfill, Fiona (Gezira Journal of Health Sciences; Vol 6 No 1 (2010), 2010)
The objectives: To confirm or refute that when the fetal cardiac activity is demonstrated on scan at less than 7 weeks gestation, the risk of miscarriage is not significantly different from the natural-background risk .To ascertain the outcome of threatened miscarriage The setting: The early pregnancy assessment unit at Sharoe Green Hospital, Preston, England, U. K. Design: The study was prospective and observational. The subject: 325 pregnant women who presented with viable pregnancies and vaginal bleeding in the first 20 weeks of pregnancy. The intervention: Transabdominal or transvaginal ultrasonography. Statistics: The statistical package, SPSS 9.0 for windows, was used and Pearson’s Chi-square test was selected to compare the groups. P ≥ 0.05. Results: Higher parity and recurrent miscarriages were associated with higher rate of miscarriage. Women presenting with viable pregnancies and moderate to heavy vaginal bleeding had a significantly higher rate of miscarriage (24.1%) compared with (9.0%) in women presenting with mild bleeding (Pearson Chi-square test = 17.516, df = 2, Asymp.sig. (2-Sided) = 0.000). In 37.5% of the women, there were significant differences in the gestational age as calculated by the scan from that calculated by the first day of the L ast- M enstrual P eriod (LMP). The rate of miscarriage (17.5%) amongst women with gestational age of less than 7 weeks was significantly higher than (9.2%) amongst women with gestational age of more than 7 weeks (Pearson Chi-square test = 7.065, df = 2, Asymp.sig. (2-Sided) = 0.029). Hematomas were associated with significantly higher rates of miscarriages (25.8%) in contrast to a rate of 10.2% amongst women without hematomas  (Pearson Chi-square test = 6.990, df = 2, Asymp.sig. (2-Sided) = 0.030). Conclusions: Moderate to heavy vaginal bleeding, a gestational age of less than 7 weeks and the demonstration of a haematoma on ultrasound scan are associated with significantly higher rates of miscarriage. Higher parity and recurrent miscarriages are associated with increased risk of miscarriage.